The Form of Culture in East Kalimantan Folklore Larangan Mersapik: Literary Antrhopological Study - Herlinda Wati; Nina Queena Hadi Putri; Alfian Rokhmansyah; Nia Novita Putri (LPPM Universitas Bumigora Mataram, 2026)
This study examines the cultural values contained in the folktale Larangan Mersapik through a literary anthropology approach. The main problem of this research is how cultural forms are represented in the story and how they reflect the community’s belief system and social life. This study aims to identify and analyze the cultural elements and cultural manifestations reflected in the folktale as a representation of local wisdom. The research uses a qualitative descriptive method with a literary anthropology approach. Data was obtained through documentation techniques by examining narrative units in the folktale that represent cultural values, social norms, belief systems, and traditional knowledge. The analysis is based on Koentjaraningrat’s concept of cultural forms, which includes ideal culture (values, ideas, and norms), social activities (patterned social actions), and physical culture (artifacts). The results show that the folktale Larangan Mersapik reflects three interconnected forms of culture. The ideal form is reflected in the belief that Mersapik is a spiritual entity related to ancestral spirits and environmental balance. The activity form appears in collective social actions such as customary deliberations and ritual ceremonies conducted to restore social harmony. Meanwhile, the physical form is represented through ritual objects and traditional tools that function not only as practical objects but also as symbolic media connecting humans with the spiritual world. These findings indicate that the folktale serves as a cultural medium that preserves traditional knowledge, moral values, and ecological awareness within the community.